Insights into the morphology and evolution of orbicules in the Spermacoce clade (Spermacoceae-Rubiaceae) and implications for systematics - Nuñez Florentín, Mariela (2023)
Fil: Nuñez Florentín, Mariela. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.